The Role of Machine Learning in 6G Wireless Networks: A Comprehensive Overview - Sreenivasulu , Gunji; Kishore , R. Sudha; Kumar , K. Kranthi; Kumar, K S Ranadheer; Rao , Adapa.Srinivasa; Badiguntla , Ramakrishna; Kasukurthi , Aravinda; Nancharaiah , B. (International Journal of Basic and Applied Sciences, 2025)
The development of 6G networks marks a major step forward in wireless communication technology, aiming to provide extremely fast data speeds, ultra-low latency, high reliability, and greater energy efficiency. Unlike previous generations, 6G is expected to be much more than just faster internet—it will enable new and advanced services like real-time remote surgery, immersive augmented and virtual reality, autonomous transportation, and smart cities. At the heart of this transformation is the use of machine learning (ML), which will be deeply integrated into the core of 6G systems. Machine learning gives networks the ability to learn from data, make decisions, and adapt to changing situations without needing constant human guidance. This will help networks become more intelligent, flexible, and efficient in delivering services to users. For example, ML can help predict when and where network traffic will be high, allowing the system to automatically allocate resources where they are needed most. It can also help detect and respond to security threats in real-time, improve the quality of service by adjusting settings based on user behavior, and reduce energy usage by optimizing the use of network devices. These capabilities will be especially important in supporting the billions of connected devices expected in the future, including sensors, robots, drones, and smart appliances. Despite these difficulties, the opportunities offered by ML in 6G are enormous. It can bring better user experiences, smarter management of network operations, and the ability to support entirely new types of services. As research and development continue, collaboration between engineers, data scientists, and policymakers will be essential to ensure that the benefits of 6G are realized while minimizing the risks. In conclusion, the integration of machine learning into 6G is not just an upgrade—it is a fundamental shift in how wireless networks are designed and operated. By making networks smarter and more responsive, ML will play a key role in shaping the future of communication and digital services around the world.
Keywords: Machine Learning, Fifth Generation, sixth Generation, Wireless Network, Algorithms